Effectiveness of School Field Introduction (PLP) Program on Improving Teaching Strategy Skills of Mathematics Education Students - Khaira, Shabna; Mauludfi, Embun (Universitas KH. Mukhtar Syafaat Banyuwangi, 2025)
This study aims to evaluate the effectiveness of the School Field Introduction Program (PLP) in improving the teaching strategy skills of mathematics education students. Using a quantitative approach, data were collected through questionnaires distributed to UIN Syarif Hidayatullah Jakarta students. According to the results, most students reacted positively to the introduction of PLP, especially in terms of their attitudes towards lesson planning, content absorption, study monitoring, and the use of technology in education. Increased self-esteem, development of teaching skills, and preparation of people for academic challenges were all considered benefits of the program. However, there were areas related to teamwork and self-assessment that needed to be developed. These results underline the importance of incorporating real experiences such as PLP into teacher training programs to develop flexible and competent instructors.